Valuasi ekonomi dan pengelolaan mangrove secara berkelanjutan di desa Jangkang Kecamatan Bantan - Rizal Muhtady; Thamrin Thamrin; Darwis Darwis (Pelantar Press, 2019)
This study aims to determine the direct economic valuation, index value and sustainability status, and strategy for the sustainability of the mangrove ecosystem in Jangkang Village. The research method of calculating direct economic valuation is carried out using a market approach. To assess the index and status of sustainability with a multidimensional scaling (MDS) approach through the ordination technique Rapid Appraisal For Status Of Mangrove (Rap-Mangrove). The results showed that in direct economic valuation, the shrimp fishing sector has a greater potential compared to other sectors. The total economic value of shrimp is IDR 1,440,000,000 / year, capture fisheries is IDR 686,400,000 / year and panglong charcoal IDR 447,500,000 / year. The multidimensional results of the index value and the status of the sustainability of the mangrove ecosystem in Jangkang Village obtained a value of 50.76 in the less sustainable category. The results of the analysis leverage show that of the 18 indicators, there are 10 sensitive indicators that affect the sustainability status of Jangkang Village. To increase the sustainability status of sensitive indicators, strategies that can be carried out include participatory rehabilitation, development of alternative livelihoods, counseling for the Akit Tribe to maintain local wisdom values, and intensive approaches to community leaders.